Long-Term Evaluation (up to 7 years) of the use of a Collagen Matrix to Treat Gingival Recession Associated with Noncarious Cervical Lesion: Report of Two Cases - Nunes, Marcelo Pereira (2021)
Introduction: Gingival recession (GR) is a relevant clinical condition due to its high prevalence worldwide, which leads to aesthetic demands and dentin hypersensitivity. Collagen matrices have been associated with different designs of coronally advanced flaps (CAFs) to treat GR defects. However, the literature lacks long-term follow-up of this treatment option. The aim of this study is to present the long-term follow-up (up to 7 years) of two GR defects (associated or not with noncarious cervical lesion) treated with a CAF and a collagen matrix (CM). Case presentation Case 1 underwent a CAF associated with a CM to treat a single GR defect. After 7 years, Case 1 presented with 3 mm of recession reduction, which corresponds with the 85.7% of root coverage. Case 2 presented two GR defects associated with noncarious cervical lesions (NCCLs). The NCCLs were partially restored with resin composite and then underwent a modified CAF for multiple defects and a CM. After 5 years of follow-up, Case 2 presented with 1.5 and 2.5 mm of recession reduction, which corresponds with the average 83.3% defect coverage. Conclusion These two cases may show that CMs can provide long-term stable outcomes in the treatment of GR defects.